2008
DOI: 10.1111/j.1468-1293.2008.00561.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of transmitted antiretroviral drug resistance in treatment‐naïve patients and factors influencing first‐line treatment regimen selection

Abstract: ObjectivesTo estimate the prevalence of transmitted antiretroviral (ARV) drug resistance, and to assess whether resistance testing influences first-line ARV regimen selection. MethodsData on patients' characteristics were collected through questionnaires. ARV drug resistance was tested by genotypic methods and defined by Quest-Stanford classification rule. Physicians reported the intended and actual treatments and the factors considered in treatment selection. ResultsTwo hundred and twenty-eight patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 26 publications
4
25
0
Order By: Relevance
“…The inherent ability of replicating HIV to revert to a drug-sensitive genotype in the absence of drug pressure makes it difficult to study in patients, especially if (i) the time, duration, and route of infection are unknown, (ii) there is no way to prove ART-naïve status, and (iii) the HIV sequence in the infecting partner is unknown. Despite these difficulties, genotypic analysis of ART-naïve patients has provided evidence that drugresistant HIV-1 is being transmitted and can result in treatment failure (15)(16)(17)(18)(19)(20)(21). Given that animal studies are the best option to overcome the inherent limitations of human studies (22), we utilized humanized mice to investigate in vivo transmission of drugresistant HIV-1.…”
mentioning
confidence: 99%
“…The inherent ability of replicating HIV to revert to a drug-sensitive genotype in the absence of drug pressure makes it difficult to study in patients, especially if (i) the time, duration, and route of infection are unknown, (ii) there is no way to prove ART-naïve status, and (iii) the HIV sequence in the infecting partner is unknown. Despite these difficulties, genotypic analysis of ART-naïve patients has provided evidence that drugresistant HIV-1 is being transmitted and can result in treatment failure (15)(16)(17)(18)(19)(20)(21). Given that animal studies are the best option to overcome the inherent limitations of human studies (22), we utilized humanized mice to investigate in vivo transmission of drugresistant HIV-1.…”
mentioning
confidence: 99%
“…Table 4 compares our data with other recent US studies documenting primary resistance in chronically infected patients. Our study had the lowest rate (5%) among these recent studies [1][2][3][4]6,7 in which the rate of resistance ranged from 8% to 18%. The distribution of resistance among the antiretroviral classes was consistent with the recently published data, which showed that NNRTI resistance prevalence was the highest, followed by NRTI and PI resistance.…”
Section: Resultsmentioning
confidence: 91%
“…[1][2][3][4][5][6][7][8] Resistance testing for chronically HIV-infected individuals is currently recommended at the time of the first evaluation and at treatment initiation. 9 The prevalence of primary resistance varies by geographic region and may be influenced by local demographics, HIV risk factors, and the penetration of antiretroviral therapy (ART) in the local area.…”
Section: Introductionmentioning
confidence: 99%
“…Several additional laboratory tests should be performed once AHI is diagnosed, including CD4 + T lymphocyte counts, HIV RNA level, screening for other STDs, and hepatitis B and C. Given the reported prevalence of transmitted drug resistance, HIV resistance testing should be strongly considered [80][81][82][83]. Limit of detection of assay for plasma viral RNA Eclipse phase approx.…”
Section: Confirmatory Testsmentioning
confidence: 99%